A Conceptual Review of Positive Teacher Interpersonal Communication Behaviors in the Instructional Context - Xie, Fei; Derakhshan, Ali (Frontiers in Psychology, 2021)
Following the recent special issue in Frontiers in Psychology, entitled “The Role of Teacher Interpersonal Variables in Students’ Academic Engagement, Success, and Motivation”, calling educational researchers worldwide to examine different teacher interpersonal communication behaviors that contribute to student-related academic outcomes, this conceptual review article is written to familiarize educational researchers, teachers, and students with main concepts in instructional communication and their role as the main pillar of successful teaching and learning processes. To this aim, by drawing on the positive psychology movement and the rhetorical and relational goal theory in instructional communication, we argue that positive teacher interpersonal communication behaviors are facilitators of a wide range of desirable student-related academic outcomes. Then, to support our argument, we provide empirical evidence. In doing so, we introduce and define seven instances of positive teacher interpersonal communication behaviors, namely teacher care, clarity, credibility, rapport with students, stroke, immediacy, and confirmation, and expound how they positively predict academic outcomes such as motivation, learning, engagement, involvement, class attendance, willingness to communicate, performance, and success in students. Subsequently, we highlight the critical role of teacher interpersonal variables in the foreign/second language classroom context. Next, we suggest some pedagogical implications with the potential to enlighten the practice of key educational stakeholders (i.e., teachers, students, teacher educators, materials developers, administrators, and teacher recruiters). At the end, the limitations in this line of research are identified, and avenues for future research on teacher interpersonal communication in both general education and language education domains are put forward for interested researchers.